2015
DOI: 10.1039/c4cc07836e
|View full text |Cite
|
Sign up to set email alerts
|

On the antibacterial mechanism of graphene oxide (GO) Langmuir–Blodgett films

Abstract: The Langmuir-Blodgett (LB) technique was used to immobilize flat graphene oxide (GO) sheets on a PET substrate to ascertain as to whether the edges of GO play an integral part in its antimicrobial mechanism. The observed antibacterial activity suggests that contact with the edges is not a fundamental part of the mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
180
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(195 citation statements)
references
References 32 publications
15
180
0
Order By: Relevance
“…Indeed, several graphene-derived substrates with oxygen-containing functional groups may produce a surplus of ROS, which can contribute to the antimicrobial effect, but it could be also correlated to a higher cytotoxicity [44,45]. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several graphene-derived substrates with oxygen-containing functional groups may produce a surplus of ROS, which can contribute to the antimicrobial effect, but it could be also correlated to a higher cytotoxicity [44,45]. …”
Section: Resultsmentioning
confidence: 99%
“…In other studies, anti-microbial activity of graphene oxide (GO) has been attributed to induction of microbial membrane damage, disturbance of the membrane potential [93] and electron transport [94], as well as oxidative stress by increased production of reactive oxygen species (ROS) [95,96]. Antibacterial properties of graphene oxide were also found to be dependent on the size of the GO sheets: larger GO sheets, wrapping bacterial cells, can effectively isolate bacteria from their environment, and show stronger antibacterial activity as compared to small GO sheets [97].…”
Section: Antifungal and Antibacterial Agentsmentioning
confidence: 99%
“…[21][22][23] For instance, graphene (and graphene oxide) has been systematically studied 24 for its antimicrobial activities, [25][26][27][28] along with its underlying molecular mechanisms. [29][30][31][32] It was revealed that graphene and graphene oxide nanosheets can cut into cell membranes, 32 extract large amount of phospholipids, 32 and create holes (pores) on cell membranes, 33 through large scale molecular dynamics simulations.…”
mentioning
confidence: 99%